Prevalence and genotype distribution of human papillomavirus infection among women aged 30-65 years in Xi'an, China: a population-based study of 14,655 women - Xiaoxiao Han; Guozhong Song; Yufang Li; Zhaoqiang Dong; Xianchun Yan; Suqing Wang; Huizhen Tian; Xiaohong Wu; Chen Li; Yi Huo (Taylor & Francis Group, 2021)
Cervical cancer is the fourth most common cancer among women worldwide in terms of both incidence and mortality. Persistent infection with high-risk human papillomavirus (HPV) has been identified as a cause of cervical intraepithelial neoplasia and invasive cervical cancer. The distribution of human papillomavirus genotypes varies regionally. To acquire baseline data on the population-based prevalence and genotype distribution of HPV infection, we investigated the molecular epidemiology of HPV infection among women in Xi'an, China. The study was conducted from September 2018 to December 2020. A total of 14,655 women aged 30-65 years were screened. The overall prevalence of HPV infection was 13.5% (95% confidence interval [CI]: 13.0-14.1%), with 10.4% of participants being positive for a single HPV type and 3.1% being positive for multiple HPV types. The prevalence of high-risk HPV (HR-HPV), low-risk HPV (LR-HPV) and mixed HPV infection was 10.1% (95% CI: 9.6-10.5%), 2.2% (95% CI: 2.0-2.4%), and 1.3% (95% CI: 1.1-1.5%), respectively. The five most frequently detected HR-HPV types were types 52 (2.6%), 16 (1.9%), 53 (1.8%), 58 (1.4%), and 51 (0.9%). The most frequently detected LR-HPV type was HPV-42 (1.1%). The prevalence and HPV genotype distribution varied by region and age. Age-specific HPV prevalence peaked in the over 60 years age group (18.8%), and Beilin District had the highest HPV prevalence (18.1%). The results of this first population-based study provide a reference for HPV-based cervical cancer screening and HPV vaccination programs in Xi'an.